Precog visions: Predicting the future with the Minority Report sociotechnical imaginary - Glenhaber, Mehitabel; Sridharan, Hamsini (Social studies of science, 2025)
The 2002 film Minority Report regularly appears in tech press articles asking whether it ‘predicted the future’. When such publications invoke the film as having ‘predicted the future’ or ‘come true’, what social and political claims are being made? How has Minority Report become a discursive tool for imagining, constructing, and criticizing sociotechnical worlds? In this paper, we evaluate the worldbuilding process and real-world trajectories of three technologies ‘from’ Minority Report, as refracted through the lens of tech journalism: gestural interfaces, targeted advertising, and predictive policing. We argue that science fiction does more than represent technologies; it participates in their social construction. Some technologies imagined in Minority Report operate as ‘diegetic prototypes’, and the journalistic witnessing public takes them up in complex ways, interpreting, misinterpreting, and remixing the technologies depicted in the film. We further argue that it is not only technologies that move between film and reality in this process, but entire sociotechnical imaginaries. We find that in tech beat interpretations of Minority Report, the interfaces between bodies and technologies reflect a Silicon Valley sociotechnical imaginary of disembodied cyborg subjects and deracialized surveillance that materially and discursively shapes how technologies depicted in the film are developed and received.